Stress Hyperglycemia Is Associated with Unfavorable Outcomes After Mechanical Thrombectomy in Patients with Acute Ischemic Stroke - Jie Gao; Xiangliang Chen; Qing Huang; Mengmeng Gu; Ye Hong; Gelin Xu (Brain Sciences)
Background: Stress hyperglycemia may deteriorate stroke outcomes, but its impact on the prognosis following mechanical thrombectomy remains unclear. This study aimed to evaluate the effects of stress hyperglycemia on in-hospital and 3-month outcomes in stroke patients with anterior circulation occlusion undergoing mechanical thrombectomy. Methods: A total of 415 patients who had mechanical thrombectomy in the anterior circulation were enrolled. The stress hyperglycemia ratio (SHR) was calculated as the fasting glucose to glycated hemoglobin ratio and was categorized into tertiles (i.e., SHR1–3). In-hospital and 3-month outcomes were compared using multivariable regression models. The impact of SHR stratified by diabetes status was evaluated and the predictive accuracy of the Totaled Health Risks in Vascular Events (THRIVE)-c risk score was explored with the inclusion of SHR. Results: Compared to the SHR1–2 groups, the SHR3 group exhibited significantly higher rates of 24 h symptomatic intracranial hemorrhage (adjusted odds ratio [aOR], 4.088; 95% confidence interval [CI], 1.551–10.772; p = 0.004) and 72 h early neurological deterioration (aOR, 3.505; 95% CI, 1.984–6.192; p < 0.001), while the incidence of post-stroke pneumonia did not differ significantly between the groups (aOR, 1.379; 95% CI, 0.838–2.268; p = 0.206). At three months, the SHR3 group had a worse distribution of modified Rankin scale (aOR, 2.261; 95% CI, 1.495–3.421; p < 0.001) and faced a higher risk of functional dependence (adjusted hazard ratio [aHR], 1.629; 95% CI, 1.230–2.158; p = 0.001) as well as all-cause mortality (aHR, 1.986; 95% CI, 1.235–3.194; p = 0.005). The adverse effects of an elevated SHR were more pronounced in non-diabetic patients, and incorporating SHR significantly enhanced the predictive accuracy of the THRIVE-c score for poor stroke outcomes. Conclusions: Stress hyperglycemia could be related to the risks of in-hospital complications and 3-month poor outcomes following mechanical thrombectomy in the anterior circulation.